Probing the Structure-Activity Relationship of an Antioxidant Tuna-Backbone Derived Peptide. (29th May 2020) - Gopinatth, Varun; Ballinger, Elaine; Kwon, Jung
Abstract: Objectives: DNA is easily degraded by reactive oxygen and nitrogen species, and once damaged can cause significant biological problems. Endogenous mechanisms exist to neutralize reactive oxygen species, but nutritional antioxidants provide extra protection against cellular damage. There is interest in identifying antioxidant peptide nutraceuticals that can provide health benefits when included in diets. Current research identifies antioxidant peptides from natural sources but often stops short of examining mechanisms for activity. An antioxidant peptide (APTBP) was previously characterized from tuna backbone protein. This study investigates the structure-activity relationship of APTBP to identify how the specific peptide sequence contributes to the antioxidant activity. Better understanding of the mechanism of antioxidant peptides can provide insight into future screens and combine with predictive software to identify potential antioxidative sequences from protein sources of interest. Methods: Peptide array was synthesized by Thermo Fisher. Modifications were chosen in broad categories with possible mechanistic impact including altering the peptide PI, disrupting the secondary structure, increasing or decreasing hydrophobicity, and increasing aromaticity. The array was tested for activity based on the ability to scavenge ABTS free radical. Results: APTBP analogs without hydrophilic, and aromatic residues showed significant loss of activity, up to 76.8%. Notably, substitution of a single tryptophan on either terminal end of the peptide resulted in up to 63.1% increased activity, while substitution of tryptophan on both ends decreased activity by 10.3%. Conclusions: The antioxidant activity of APTBP is likely the result of a delicate interplay between amino acids in the peptide, but tryptophan residues had an important impact on activity. Tryptophan has an indole side chain, and is a non-polar, aromatic amino acid. The antioxidant activity of ABTBP is significantly linked to the presence of tryptophan, indicating that aromaticity and electron sharing contributes majorly to the ability of ABTBP to scavenge free radicals. The results from this study can help in future research that aims to identify other potential antioxidant peptides as well as ways to increase antioxidant activity of existing peptides. Funding Sources: OSU Honors College.